Mendelian randomization analysis reveals causal effects of food intakes on inflammatory bowel disease risk - Chen, Bingxia; Han, Zemin; Geng, Lanlan (Frontiers in Immunology, 2022)
Traditional observational studies have indicated a link between specific food intakes and inflammatory bowel disease (IBD), but the nature of such links remains unknown. We sought to assess the potential causal relationship between food intakes and IBD risk using Mendelian randomization methods. This study used summary statistics data from large-scale genome-wide association studies (GWAS) on food intakes, Crohn’s disease (CD), and ulcerative colitis (UC). In the primary analysis, we used the inverse variance-weighted method, as well as five other Mendelian randomization methods, including MR Egger, weighted median, maximum likelihood, and weighted mode, to determine whether exceptional food was causal for CD and UC. The primary analysis showed that high consumption of processed poultry (OR, 3.696; 95% CI, 1.056-12.937; P =0.041) and cereal (OR, 2.449; 95% CI, 1.094-5.482; P = 0.029) had a significant causal association with CD, while high oily fish intake level was found statistically significantly associated with the risk of UC (OR, 1.482; 95% CI, 1.002-2.194; P =0.049). This MR study provides evidence of a potential causal link between certain food intake and CD, UC.